Stanton in her own time : a biographical chronicle of her life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Baker, Noelle A. (Noelle Annette), 1964- (Writers in their own time (University of Iowa Press), 2016)
Among nineteenth-century women's rights reformers, Elizabeth Cady Stanton (1815-1902) stands out for the maternal and secular advocacy that shaped her activism and public reception. A wife and mother of seven, she was also a prolific writer, transatlantic women's rights leader, popular lecturer, congressional candidate, canny historian, and freethought champion. Her lifelong interest in women's sexual and reproductive rights and late efforts to reform institutional religion are as relevant to our time as they were to her own. Stanton's professional life lasted a half-century, ranging from antebellum women's rights organization and oratory, to a post-Civil War career as a lyceum lecturer, to a late-century role as an incisive religious and cultural critic. Acutely aware of the medical, religious, legal, and educational barriers to women's independence, she advocated for married women's right to vote, obtain a divorce, gain custody of their children, and own property. As she grew more radical over the years, she also demanded judicial reform, the separation of church and state, free love, progressive coeducational opportunities, and women's right to limit their fertility. In this richly contextualized collection of primary sources, Noelle A. Baker brings together accounts of Stanton's life and ideas from both well-known and recently recovered figures. From the teacher chiding an assertive young woman to erstwhile allies worrying about her growing radicalism, their voices paint a vivid portrait of a woman of vaunting ambition, powerhouse intellect, and her share of human failings.